The Influence of Ag Addition and Different SiO2 Precursors on the Structure of Silica Thin Films Synthesized by the Sol–Gel Method - Anna Adamczyk; Tomasz Brylewski; Patryk Szymczak (Molecules)
In this work, the structure of silica thin films synthesized with three different SiO2 precursors and obtained by the sol–gel method and dip coating technique was studied. Additionally, the influence of Ag addition on the obtained silica sols and then gel structure was investigated. Silica coatings show antireflective properties and high thermal resistance, as well as hydrophobic or hydrophilic properties. Three different silica precursors, TEOS (tetraethylorthosilicate), DDS (dimethyldietoxysilane) and AerosilTM, were selected for the synthesis. DDS added to silica sol act as a pore size modifier, while Ag atoms are known for their antibacterial activity. Coatings were deposited on two different substrates: steel and titanium, dried and annealed at 500 °C in air (steel substrate) and in argon (titanium substrate). For all synthesized films, IR (infrared) spectroscopic studies were performed together with GID and XRD (Grazing Incidence Diffraction, X-ray Diffraction) measurements. The topography and morphology of the surface were traced by SEM and AFM microscopic methods, providing information on the samples’ roughness, particle sizes and thickness of the particular layers. The wetting angle values were also measured. GID and XRD measurements pointed to the distinct contribution of an amorphous phase in the samples, allowing us to recognize the crystalline phases and calculate the silver crystallite sizes. The FTIR spectra gave information on the first coordination sphere of the studied samples.